The Dual Role of Echocardiography in the Diagnosis of Acute Cardiac Complications and Treatment Monitoring for Coronavirus Disease 2019 (COVID-19) - Vrettou, Agathi-Rosa; Parissis, John; Ikonomidis, Ignatios (Frontiers in Cardiovascular Medicine, 2020)
Coronavirus Disease 2019 (COVID -19) pandemic, being caused by an easily and rapidly spread novel betacoronavirus, has created a state of emergency for people, scientific community, health systems and states, while its global financial consequences are unfolding. Cardiovascular complications have been reported for COVID- 19 patients with or without preexisting cardiovascular risk factors or established disease. ECG biomarkers may raise the suspicion of cardiac involvement. However, transthoracic echocardiography is a fast and reliable bedside method to support diagnosis of cardiac complications including pericarditis, myocarditis and pulmonary embolism. Early detection of cardiac dysfunction by speckle tracking echocardiography during off-line analysis may be used to identify a high risk population for development of heart failure in acute setting. Precaution measures are mandatory for operators and equipment to avoid viral dispersion. No specific treatment is yet available for severe acute respiratory syndrome coronavirus 2 (SARS-CoV 2) therefore a variety of antiviral, immune modifying and antioxidant agents are under intense investigation. Echocardiography including assessment of myocardial deformation may provide a useful tool to monitor the effects of the various treatment regimens on cardiac function both acutely and in the long term.